2009
DOI: 10.1038/ejhg.2009.158
|View full text |Cite
|
Sign up to set email alerts
|

Study of smell and reproductive organs in a mouse model for CHARGE syndrome

Abstract: CHARGE syndrome is a multiple congenital anomaly syndrome characterised by Coloboma, Heart defects, Atresia of choanae, Retardation of growth and/or development, Genital hypoplasia, and Ear anomalies often associated with deafness. It is caused by heterozygous mutations in the CHD7 gene and shows a highly variable phenotype. Anosmia and hypogonadotropic hypogonadism occur in the majority of the CHARGE patients, but the underlying pathogenesis is unknown. Therefore, we studied the ability to smell and aspects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 34 publications
(48 reference statements)
4
47
0
Order By: Relevance
“…Thus, we mated Plxnd1 +/-females with Chd7 +/-males (41) and examined the innervation of the ME in single and compound heterozygous mice. We found that fewer GnRH-positive neuron fibers projected to the ME in the hypothalamus of their Chd7 +/-male offspring compared with that seen in their WT littermates ( Figure 10E, top panels), consistent with previous observations (42). Importantly, the finding that jci.org Volume 125 Number 6 June 2015…”
Section: Sema3esupporting
confidence: 81%
“…Thus, we mated Plxnd1 +/-females with Chd7 +/-males (41) and examined the innervation of the ME in single and compound heterozygous mice. We found that fewer GnRH-positive neuron fibers projected to the ME in the hypothalamus of their Chd7 +/-male offspring compared with that seen in their WT littermates ( Figure 10E, top panels), consistent with previous observations (42). Importantly, the finding that jci.org Volume 125 Number 6 June 2015…”
Section: Sema3esupporting
confidence: 81%
“…Mice with complete Chd7 deficiency mirror the observed human phenotypes (delayed puberty, genital hypoplasia, hypogonadotropism) and display neurodevelopmental defects, including reduced GnRH neurons in the hypothalamus and reduced expression of FGFR1 in the olfactory placode (30,31). Recent work also suggests that CHD7 regulates genes involved in neural crest guidance (32), and there is increasing evidence that KS may also result from impaired neural crest guidance (33).…”
Section: Discussionmentioning
confidence: 99%
“…Mice with heterozygous Chd7 mutations show semicircular canal defects, septal heart defects, cleft palate, choanal atresia, hyposmia, olfactory bulb anomalies, testes hypoplasia, hearing loss, and low body weight [Bosman et al, 2005;Adams et al, 2007;Hurd et al, 2007, Layman et al, 2009;Bergman et al, 2010 ]. Other CHARGE features, e.g.…”
Section: Discussionmentioning
confidence: 99%